Кровавый снег декабря - Шалашов Евгений Васильевич (История, которой не было, 2010)
Экземпляры: РБ (20190306) / Инвентарный номер: 56574 / Цена: 100.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ш 18 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6